Filling nanoporous polymer thin films: an easy route toward the full control of the 3D nanostructure. Issue 11 (22nd January 2016) - Li-Destri, G.; Tummino, A.; Malfatti Gasperini, A. A.; Parellada Monreal, L.; Messina, G. M. L.; Spampinato, V.; Ceccone, G.; Konovalov, O.
Abstract : A fully controllable interpenetrated 3D nanostructure is obtained by filling a nanoporous polymer ultrathin film with a second organic component. Abstract : A novel approach enabling the full control of the 3D nanostructure of polymer thin films is presented. An ordered nanoporous polymer film is obtained using a nanoparticle monolayer as template. The pores are then filled with a second organic component via spin coating which, by modulating the deposition parameters, enables the control of the filling degree with nanometric precision.